The effects of tax and expenditure limits on state fiscal reserves. (April 2017) - Maher, Craig S; Stallmann, Judith I; Deller, Steven C; Park, Sungho
To help policy makers manage expenditures during periods of economic downturns, most states have formal budget stabilization funds and unreserved fund balances. Using indices of tax and expenditure limitations laws restrictiveness, we examine the relationship between tax and expenditure limitations and state reserves for years 1992–2010 to help determine the extent to which tax and expenditure limitations constrain or in other ways affect how states manage fiscal reserves. This time period is particularly relevant because it includes two recessions and most states had budget stabilization funds and tax and expenditure limitations. Findings suggest that state-constructed tax and expenditure limitations have little effect on state capacity to react to fiscal shocks.